Analisis pengaruh indeks saham asing terhadap indeks harga saham gabungan dengan pendekatan Error Correction Model - Nuraeni, Risky; Panjawa, Jihad Lukis (Nur Science Institute, 2021)
The Composite Stock Price Index (IHSG) is a composite index of many shares listed on the stock exchange and their movements show conditions that occur in the capital market. JCI is confident of macroeconomic factors and foreign exchange indexes. The purpose of this study was to analyze the effect of the Dow Jones Index, the Straits Time Index, the Hang Seng Index, the Nikkei 225 Index, and the FTSE 100 Index on the composite price index. The research method used is the Error Correction Model (ECM). In the short term, the DJIA and FTSE 100 variables have a positive effect on the JCI, the STI and Hang Seng variables have no significant on the JCI, while the Nikkei 225 has a negative effect on the JCI. In the long term, the DJIA and STI variables have a positive effect on the IHSG, the JSI and FTSE 100 variables have no effect on the IHSG, while the Nikkei 225 variable has a negative effect on the JCI.